Making Specific Plan Improves Physical Activity and Healthy Eating for Community-Dwelling Patients With Chronic Conditions: A Systematic Review and Meta-Analysis - Lin, Hui; Yu, Ping; Yang, Min; Wu, Dan; Wang, Zhen; An, Jiye; Duan, Huilong; Deng, Ning (Frontiers in Public Health, 2022)
Background. Implementation intention, formed by making specific action plan, has been proven effective in improving physical activity (PA) and dietary behavior (DB) for the general, healthy population, but there has been no meta-analysis of their effectiveness for patients with chronic conditions. This research aims to analyze several explanatory factors and overall effect of implementation intention on behavioral and health-related outcomes among community-dwelling patients. Methods. We searched CIHNAL (EBSCO), PUBMED, and five other databases for eligible studies. Random-effects meta-analysis was conducted to estimate effect sizes of implementation intention on outcomes including PA, DB, weight and body mass index. And the eligible studies were assessed by the Cochrane Collaboration's tool for risk of bias assessment. Sensitivity analysis adopted sequential algorithm and p-curve analysis method. Results. A total of 35 English language studies were identified. Significant small effect sizes of the intervention were found for PA (standard mean difference [SMD] 0.23, 95% confidence interval [CI] [0.04, 0.42]) and for DB outcome (SMD -0.25, 95% CI [-0.35, -0.16]). In moderation analysis, the intervention was more effective in improving PA for men (p = 0.004), older adults (p = 0.002) and patients without obese/overweight condition (p = 0.029) and when the intervention was delivered by healthcare provider (p = 0.003). Conclusions. Implementation intentions are effective in improving PA and DB for community dwelling patients with chronic conditions. The review provides evidence to support the future application of implementation intention intervention. Besides, the findings from this review offer different directions to enhance the effectiveness of this brief and potential intervention in improving patients' PA and DB.